Broadband dual-polarized aperture-coupled patch antennas with modified H-shaped coupling slots. - Kin-Lu Wong
This paper presents a new design of aperture-coupled patch antennas with modified H-shaped coupling slots for achieving dual-polarization radiation with high isolation over a wide bandwidth. By using the proposed coupling slots, whose two upper side arms are bent inward with a proper angle, the isolation between the two feeding ports of the patch antenna can. greatly be improved, compared to the case with conventional H-shaped coupling slots. Also, when using a pair of modified H-shaped coupling slots for each feeding port, the isolation can further be improved; a high degree of isolation (< -34 dB) over the entire impedance bandwidth greater than 15% and good cross-polarization level (> 20 dB) for the two polarizations can be achieved. Details of the proposed design and experimental results are presented and discussed
Keywords: 1500 to 2000 MHz; Aperture-coupled patch antennas; Broadband patch antennas; Cross-polarization level; Dual-polarized antennas; Impedance bandwidth; Isolation; Modified H-shaped coupling slots; Radiation patterns